2012
DOI: 10.1111/j.1365-2125.2011.04090.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a single nucleotide polymorphism in SLCO1B1 on the pharmacodynamics of pravastatin

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• The SNP rs4149056 is associated with altered statin pharmacokinetics and increased risk of statin intolerance. LDL-cholesterol lowering by simvastatin is also affected by rs4149056 but differences between the genotypes are small. Studies of the effect of rs4149056 on pravastatin pharmacodynamics have been inconclusive. WHAT THIS PAPER ADDS• rs4149056 was not associated with an altered lipid or CRP response to 40 mg day -1 pravastatin in more than 600 high risk men from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 13 publications
1
11
1
Order By: Relevance
“…The SLCO1B1 c.521T > C variant is well related to the risk of side effects of statin treatment, but conflicting results have been reported about its influence on the lipid‐lowering effects of statins. In some works, the C allele was associated with lower reductions of non‐HDL cholesterol, but in others, this effect was not observed, as is the case in our study. CYP3A4 variant causes a reduction in statins bioavailability, and some authors have related it to lower reductions of LDL cholesterol after statin treatment, although we could not find it relevant.…”
Section: Discussionsupporting
confidence: 46%
“…The SLCO1B1 c.521T > C variant is well related to the risk of side effects of statin treatment, but conflicting results have been reported about its influence on the lipid‐lowering effects of statins. In some works, the C allele was associated with lower reductions of non‐HDL cholesterol, but in others, this effect was not observed, as is the case in our study. CYP3A4 variant causes a reduction in statins bioavailability, and some authors have related it to lower reductions of LDL cholesterol after statin treatment, although we could not find it relevant.…”
Section: Discussionsupporting
confidence: 46%
“…To support our findings, some data indicate that the presence of the 521 T C non-synonymous SNPs in the SLCO1B1 gene has a weaker statin-induced reduction of LDL-C [19][20][21] . Conversely, other data suggest that there is no statistically significant difference among patients with wild type and 521 T C variants of the SLCO1B1 gene in the statin-induced lipid-lowering effectiveness [22][23][24][25][26][27] . Additionally, some confounding factors exist, such as differences in study quality, demographic characteristics of the subjects (age, gender, race, etc.…”
Section: Discussionmentioning
confidence: 87%
“…For 521 T C, some trials identified that the polymorphism modulated the lipidlowering effectiveness of HMG-CoA reductase inhibitors [19][20][21] . Conversely, some trials did not find a significant effectiveness [22][23][24][25][26][27] . In addition, Hedman et al found that decreases in the total and low-density lipoprotein cholesterol by pravastatin were significantly smaller, and the increase in the high-density lipoprotein cholesterol (HDL-C) was greater in transplant recipients with the 521TC genotype compared with patients with the 521TT reference genotype 28) .…”
Section: Exclusion Criteriamentioning
confidence: 96%
See 1 more Smart Citation
“…In another pediatric population described in the study by Hedman et al that included heart transplant recipients treated with statins, similar increases were associated with the C allele at the 521T→C (rs4149056) locus, also in SLCO1B1 [60]. Fitting the pattern of inconsistency in pharmacogenetic studies of statins, a candidate gene study of the SLCO1B1 521T→C (rs4149056) mutation in adults failed to replicate the differential changes in HDL-C [61]. In addition, the rs4149056 variant was shown to be unrelated to pitavastatin-mediated HDL-C changes in a Chinese population [62].…”
Section: Genetic Modifiers Of Hdl-c Response To Drug Treatmentmentioning
confidence: 99%